Interfaces sensoriais sem toque: poéticas sistêmicas e música interativa - Teles, Paulo César da Silva (2009)
This PhD thesis aims to point-out and map into our context, artistic tendencies basedon communication technologies that are supported by sensorial interfaces (triggered by gestures, touch and sound). The hypothesis realms that human-machines interactions shall be mediated by bodies-responsive touchless interfaces, without any device aid, like mouse, keyboards and many others. Our research has been supported by systemic works and researches - especially from the Claudia Gianetti, Esteves de Vasconcellos and Mark Hansen ones - and analyses highlighted artworks based-on digital media from Sterlac; Carmem Franinovic and Yon Visel; Myron Krueger; John Cage and Merce Cunnighan. Thus, we also propose artistic installations projects and a new approach of interactive music based-on our own touchless sensorial interface prototype. At our prototype and artworks, presence, gestuality and movements caused by the interactors, are mapped in a tridimensional space. Within this environment, people are detected by sensors that transform the triggered signals onto sound and images (generated and transformed) in real time, that sign irreversible imbrications between art and communication, and confirm our central issue